CLINICO-HEMATOLOGICAL AND MUTAGENIC CHANGES INDUCED BY ARSENIC AND COPPER SULPHATE IN ADULT POULTRY MALES - A. Ghaffar; R. Hussain; A. Khan; R. Z. Abbas; M. Asad (Journal of Animal and Plant Sciences, 2015)
The present experimental study was conducted to investigate the clinico-hematological and mutagenic changes induced by concurrent oral administration of arsenic and copper sulphate in adult poultry males. After acclimatization, a total of 28birds were randomly divided into seven equal groups. All the experimental birds received arsenic and copper sulphate alone and in combinations at different doses for 30 days in the feed. Blood samples were collected from each bird at days 10, 20 and 30 of the experiment. Various clinical signs like decreased feed intake, body weight, ruffled feather, depression, dullness, ocular discharge, open mouth breathing, diarrhea and pale comb were observed at higher levels of arsenic and copper sulphate. In treated birds,the values of total erythrocytes counts, total leukocyte counts, hemoglobin concentration and mean corpuscular hemoglobin concentration were significantly decreased, while packed cell volume and mean corpuscular volume increased.Moreover, frequency of erythrocytes with micronuclei, blabbed, lobed, notched and cells with nuclear remnants were significantly increased compared to controls. From the results of this study it can be concluded that arsenic and copper sulphate alone at higher levels and in combination even at lower levels have severe clinico-hematological and mutagenic effects in adult male birds.
Keywords: Birds; Copper sulphate; Arsenic; Hematology; Micronuclei; Nuclear remnants